Identification of risk factors in pre-term infants with abnormal general movements - Domagalska-Szopa, Małgorzata; Szopa, Andrzej; Serrano-Gómez, María Eugenia; Hagner-Derengowska, Magdalena; Behrendt, Jakub (Frontiers in Neurology, 2022)
Introduction This study aimed to investigate the relationship between prenatal, perinatal, and postnatal risk factors for neurodevelopmental impairment (NDI) with the outcomes of General Movement (GM) Assessment (GMA) in pre-term infants at 3–5 months of age. We sought to identify the risk factors associated with the predictors of psychomotor development in pre-term newborns, such as normal fidgety movements (FMs), absent FMs, or abnormal FMs, assessed during the fidgety period of motor development. Methods The SYNAGIS program (prophylactic of Respiratory Syncytial Virus Infection) was used to identify risk factors for the development of neuromotor deficits in 164 pre-term infants who were at high risk of developing these deficits. Based on the GMA, all participants were divided into three groups of infants who presented: (1) normal FMs; (2) absent FMs; and (3) abnormal FMs. Results The results of the current study suggest that abnormal GMs not only indicate commonly known factors like birth asphyxia (BA), respiratory distress syndrome (RDS), periventricular leukomalacia (PVL), intraventricular hemorrhage (IVH) grades 3–4, but also predict the development of motor impairments. In the present study, several specific risk factors including bronchopulmonary dysplasia (BPD), infertility treatments, maternal acute viral/bacterial infections during pregnancy, and elevated bilirubin levels were identified as attributes of an atypical fidgety movement pattern. Conclusions Additional clinical data, such as risk factors for NDI associated with early predictors of psychomotor development in pre-term newborns, i.e., absent or abnormal FMs, may be helpful in predicting neurological outcomes in pre-term infants with developmental concerns in the 1st month of life.